ELITISME ALGORITMA GENETIKA PADA FUNGSI NONLINEAR DUA PEUBAH - Adriana Fanggidae; Emerensye S Y Pandie (Universitas Nusa Cendana, 2020)
The evolutionary operator in the genetic algorithm (GA) does not guarantee that the quality of individuals from generation to generation is always good. Elitism maintains the preservation of the best individual traits from generation to generation by multiplying the best set of individuals. In this paper, it is determined the number of copies that need to be done on the best individual. Tests were carried out on five nonlinear functions with two variables and the result was that the best individual multiplication was able to provide the best solution.